Salivary testosterone and cortisol levels to assess conditioning training program in rugby union players - Pacini, S.; Branca, J. J. V.; Gulisano, M.; Levi Micheli, M.; Ceroti, M.; Ruggiero, M.; Morucci, G. (Medicina dello Sport, 2014)
Aim. Aim of the present study was to prevent overtraining and to ensure that the athletic training program will result in performance improvements, regular performance tests as well as heart rate evaluation and questionnaires are necessary. However, none of them are routinely performed on regular basis mainly for their interference with the session training, thus leading to the risk of an over-reaching which in turn may result in an overtraining. In this study we evaluate the possibility to monitor the development of the training program of high level rugby players by a simple, non-invasive and fast salivary testosterone and cortisol measure. Methods. Testosterone and cortisol samplings were performed in several moments of the preseason training program. Measures were correlated with anthropometric evaluations performed by bioelectrical impedance analysis before and after the training program. To assess a potential role of genetic, athletes were also genotyped for ACTN3 and ACE gene polymorphisms. Results. Data from this study show that hormone salivary measures correlate with changes in anthropometric values during the training program. No correlations were observed between genotypes and variations in hormone levels; however, ACE genotype correlates with the different team position of rugby players. Conclusion. Hormone salivary measures represent a valid, fast, non-invasive and stress-free system of monitoring the athletic preparation.